Genetic diversity of Escherichia coli Isolated from rodents by using pulsed-field gel electrophoresis (PFGE) - Siti Nursyafikah, Binti Bustaman (Universiti Malaysia Sarawak (UNIMAS), 2012)
Escherichia coli is one of the bacteria which can cause zoonoses diseases to human, an emerging public health concern in most countries of the world. This study was carried out to assess genetic diversity between E. coli in rodents from different habitats using Pulsed-Field Gel Electrophoresis (PFGE). In addition, this study aimed to determine if PFGE method is capable of differentiating the collection of E. coli from different habitats. Molecular subtyping by PFGE were performed on 22 confirmed E. coli isolates in rodents from Nanga Merit, Sibu, Matang and Kubah, The 22 E. coli isolates digested with XbaI generated 6 to 13 bands, producing a total of 20 different DNA banding patterns with an untypeable (UT) isolate. The banding sizes of the isolates ranged approximately from 28.8 kb to 668.9 kb. Analysis of resultant banding pattern of PFGE profiles were manually analyzed for presence (1) or absence (0) of a distinct band. The data obtained were further analyzed using RAPDistance version 1.04. The dendrogram generated shows that the isolates were clustered into 3 main cluster which then divided into more subclusters. The analysis of the relationship of E. coli from different habitats revealed that the average percentage of similarities of the 21 E. coli isolates were 47.10% which was low. This indicated that the 21 E. coli isolates were fairly heterogenous. An E. coli strain also found to have probably related strains to the pathogenic E. coli O157:H7 which show 3 distinct bands to the positive control of E. coli O157:H7.